2012
DOI: 10.1007/s12663-012-0340-3
|View full text |Cite
|
Sign up to set email alerts
|

Versatility of Titanium 3D Plate in Comparison with Conventional Titanium Miniplate Fixation for the Management of Mandibular Fracture

Abstract: Background In the present study, 20 patients with mandibular fracture were included to evaluate the versatility of titanium 3D plate in comparison with conventional titanium miniplate fixation. Methods The patients were alternatively allocated to either the 3D plate group or Miniplate group. The patients were evaluated for the clinical assessment of mobility after fixation, pre and post-surgical occlusal relationship, adequacy of reduction on post operative radiograph and any post surgical complications. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 14 publications
8
46
1
Order By: Relevance
“…At the end of 3 months both groups had completely satisfactory bone healing. A similar healing period was evident on radiographic assessment criteria mentioned by Bouloux et al [1] and Malhotra et al [22] in their comparative study on 3D plates versus miniplates.…”
Section: Discussionsupporting
confidence: 72%
“…At the end of 3 months both groups had completely satisfactory bone healing. A similar healing period was evident on radiographic assessment criteria mentioned by Bouloux et al [1] and Malhotra et al [22] in their comparative study on 3D plates versus miniplates.…”
Section: Discussionsupporting
confidence: 72%
“…These results were highly significant at all post operative period in our study. A result of this study is in accordance with study of Jain et al (31) Malhort et al (18) and Khalifa et al (32) .…”
Section: Discussionsupporting
confidence: 92%
“…This was assessed using a score from 1 to 3 as descried by Malhorta et a1. (18) . Score 3: Radiological evidence of precise anatomic reduction in the fracture site.…”
Section: Evaluation Of Fixation Techniques In Anterior Mandibular Framentioning
confidence: 99%
“…Radiograph was taken preoperatively, on 1 st postoperative day ( Figure 2) and on 90 th postoperative day ( Figure 3). Radiological Assessment with Postoperative Radiographs (OPG) was done according to Malhotra et al 8 and scores given as shown in Table 1. Satisfactory No discrepancy between pre trauma occlusion and postoperative occlusion in molar or canine region Mildly deranged Discrepancy of 1 -2mm between pre trauma occlusion and postoperative occlusion in molar or canine region Deranged Discrepancy more than 2mm between pre trauma occlusion and postoperative occlusion in molar or canine region…”
Section: Resultsmentioning
confidence: 99%